Anmeldelser - Strohmann, Nicole K. (Danish Yearbook of Musicology, 2005)
Review of: Jens Hesselager: Making Sense of Sounds. Nineteenth- and Twentieth-Century Ideas of Instrumentation. Copenhagen: Dansk Musik Tidsskrifts Forlag, 2004